Data from the study of CdS:Al thin films grown by the method of chemical bath deposition after aging (2020)
(Eng) This article present the data of the study of the structural, optical and vibrational properties of CdS:Al thin films synthesized by chemical bath deposition (CBD) method after aging. The samples were characterized by X-ray diffraction, UV-vis and photoluminescence spectroscopy, and Raman spectroscopy. X-ray diffraction pattern of the samples disclosed hexagonal crystalline structure of CdS. The crystallite size was estimated for each thin film. The energy band gap was calculate using the Tau plot method. The samples present defects in their structure. A detailed study on the structure was carry out in the region of 200 to 800 cm-1, where the 1LO and 2LO phonon modes are presents. The data have not been reported nor discussed for now.